2022
DOI: 10.1002/wcc.802
|View full text |Cite
|
Sign up to set email alerts
|

A review of air travel behavior and climate change

Abstract: Air transport challenges the world's net-zero carbon ambitions. The sector has consistently grown and causes warming as a result of both CO 2 and other, short-lived emissions. Two principal solutions have been proposed to reduce the contribution of aviation to climate change: innovations of technology and the development of interventions to trigger behavioral change. Technological innovations include new propulsion technologies and the use of sustainable aviation fuels. Behavioral change includes flight avoida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 74 publications
1
23
0
Order By: Relevance
“…Finally, modal shifts away from aviation may be an important strategy. It has been shown that many air travel decisions reflect wants more than needs, and some may be avoided by lower-emitting options with competitive cost and convenience . Most notably, China has developed the longest electrified high-speed railway network in the world; already lower emitting per passenger-kilometer than air travel, it will become more so as the capacity share of renewable power generation continues to grow .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, modal shifts away from aviation may be an important strategy. It has been shown that many air travel decisions reflect wants more than needs, and some may be avoided by lower-emitting options with competitive cost and convenience . Most notably, China has developed the longest electrified high-speed railway network in the world; already lower emitting per passenger-kilometer than air travel, it will become more so as the capacity share of renewable power generation continues to grow .…”
Section: Resultsmentioning
confidence: 99%
“…On-road transportation, including cars, trucks, and buses, is responsible for the majority of GHG emissions associated with transportation. Due to the altitude at which emissions are released, air travel has a much greater impact per unit of emissions than other modes of transportation [70].…”
Section: Global Climate Change and Public Health Nexusmentioning
confidence: 99%
“…This suggests the need for stronger policies supporting society-wide lifestyle changes in key domains. These include, but are not limited to, reducing car dependence (Mattioli et al 2020) and improving conditions for walking, cycling, and public transportation, increasing taxes and removing subsidies in aviation (Gössling and Dolnicar 2022), promoting plant-based diets, changing the subsidies and taxes related to meat production, and subsidizing investments in the energy efficiency of buildings. Overall policies should support consumption of goods and services with low carbon intensity, and, vice versa, taxation and other tools available for the decision-makers should be utilized to increase the prices of carbon-intensive goods and services, and to decrease the prices of the lowintensity options.…”
Section: Policy Outlookmentioning
confidence: 99%